Case Note: ‘Chris Van Hollen, Jr., v Federal Election Commission (30.03.2012)' - Antonios Kouroutakis (UCL Journal of Law and Jurisprudence, 2015)
Legal authority agencies have to tailor primary legislation based on shifts in legal precedent, as is the norm in case law. In the first instance, the question presented before the District Court of the District of Columbia in the Chris van Hollen case was whether the Federal Election Commission (‘FEC’) exceeded its statutory authority by promulgating a regulation that narrowed the disclosure rules of the Bipartisan Campaign Reform Act (‘BCRA’), 2 U.S.C. § 434(f)(2)(E) and (F). This case presents what appears to be the original instance of whether an agency may promulgate regulations that modify existing law to fit changed circumstances. Particularly, it calls into question whether an agency may narrow a statutory provision with the purpose of addressing a change in the statute’s breadth prompted by the legal precedent established through a Supreme Court ruling. Read more